„Zbyt ciężkie skutki natychmiastowego wykonania kary” jako podstawowa przesłanka fakultatywnego odroczenia wykonania kary pozbawienia wolności - Mrozek, Kamila (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The paper focuses on the issues related to a conditionally suspended imprisonment sentences. The subject matter of the paper concerns one of the legal basis stipulated in Art. 151 § 1 of the Polish Executive Penal Code, that is asituation whereby immediate execution of imprisonment would lead to excessively adverse effects for the convicted offender or his/her family. The subject matter has been analysed not only through the dogmatic but also practical approach. It has become the point of interest of the system of justice, which is reflected in an extensive base of judicial decisions presented in the paper.
Keywords: kara pozbawienia wolności; skazany przestępca; warunkowa przesłanka; nadmiernie niekorzystne skutki